Hospitalization costs and estimates of direct and indirect economic losses due to injury sustained in road traffic crashes: Results from a one-year cohort study in three European countries (The REHABILAID project). (October 2017) - Papadakaki, Maria; Stamouli, Maria-Aggeliki; Ferraro, Ottavia E; Orsi, Chiara; Otte, Dietmar; Tzamalouka, Georgia; von der Geest, Marco; Lajunen, Timo; Özkan, Türker; Morandi, Anna; Kotsyfos, Vangelis; Chliaoutakis, Joannes
Introduction: The financial cost of injuries sustained in road traffic crashes is high for victims, families and national budgets, but there is limited information on the cost of injury from the victims' perspective, especially in terms of the hard-to-reach multi-trauma patient population such as those admitted to the intensive care units of hospitals. Materials and methods: The current study received funding by the European Commission Directorate-General Mobility and Transport. It is a prospective, prevalence-based, cost-of-illness study. Participants admitted in the intensive care units of seven public hospitals in Greece, Germany and Italy because of injuries from road traffic crashes, during one year, were enrolled in the study. Patients were followed-up for one year after the intensive care unit admission to report emerging direct and indirect costs related to their injury. Results: A total of 120 people were enrolled. Males, those aged 25–49, motorcyclists and those severely injured (Maximum Abbreviated Injury Scale (MAIS) 3+) with highest severity located at the central part of the body, accounted for the highest percentages of both the direct and indirect injury costs. The highest average direct costs were for females, those aged 50–64, pedestrians and those slightly injured (MAIS 1 or 2) with highest severity at the central region of the body. Males, patients aged 25–49, car passengers and truck drivers as well as those slightly injured (MAIS 1 or 2) with highest severity at multiple locations were over-represented in the average indirect costs. Conclusions: Those groups that account for a high percentage of injury costs should be targeted in health policy initiatives.